How Much Difference Does Household Energy Source Selection Make in Winter CO2 Emissions? - Matsumoto, Shigeru (Frontiers in Climate, 2022)
Households use various energy sources for many purposes. Past studies have not investigated how much CO2 emissions change when households with similar socioeconomic characteristics choose different energy source combinations. In this study, we estimate the difference household energy source selection makes in winter CO2 emissions through a microdata analysis of 29,887 households randomly selected from whole Japan. Since socioeconomic characteristics of households affect both energy source selection and energy consumption, the impact of energy source selection on CO2 emissions cannot be assessed by simply comparing CO2 emissions among households using different energy sources. Therefore, we employ a selection bias correction model characterized by two stages, energy source selection and energy consumption. Our empirical results reveal that households using various energy source combinations increase CO2 emissions at different speeds with decreases in temperature. Households primarily using electricity and kerosene increase CO2 emissions faster than households simultaneously using gases. This result casts doubt on the promotion of fully electrified houses and at the same time encourages gas use in winter.